2010
DOI: 10.1007/s10827-010-0268-x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of two cluster solutions in pulse coupled networks of neural oscillators

Abstract: Phase response curves (PRCs) have been widely used to study synchronization in neural circuits comprised of pacemaking neurons. They describe how the timing of the next spike in a given spontaneously firing neuron is affected by the phase at which an input from another neuron is received. Here we study two reciprocally coupled clusters of pulse coupled oscillatory neurons. The neurons within each cluster are presumed to be identical and identically pulse coupled, but not necessarily identical to those in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…By clustering we do not mean spatial clustering (cultures that exhibit YMO occur in well-mixed bioreactors), but temporal clustering -cohorts of cells traversing the CDC in near synchrony (see Figure 1). The mathematical results in Boczko et al (2010) are similar to those in Chandrasekaran, Achuthan, and Canavier (2011) where, in a different context, it was observed that reciprocal coupling can stabilize a 2-cluster solution by enforcing synchrony within clusters that would not synchronize in isolation.…”
Section: Introductionsupporting
confidence: 68%
“…By clustering we do not mean spatial clustering (cultures that exhibit YMO occur in well-mixed bioreactors), but temporal clustering -cohorts of cells traversing the CDC in near synchrony (see Figure 1). The mathematical results in Boczko et al (2010) are similar to those in Chandrasekaran, Achuthan, and Canavier (2011) where, in a different context, it was observed that reciprocal coupling can stabilize a 2-cluster solution by enforcing synchrony within clusters that would not synchronize in isolation.…”
Section: Introductionsupporting
confidence: 68%
“…Synchronization was not evident at weak values for the connectivity between modules, likely due to the inability of weak coupling strengths to overcome the effects of noise. The applicability of the methods presented herein is limited only by the ability to measure the appropriate PRCs, by the requirement that the coupling be effectively pulsatile, and the restriction to only two oscillators unless the dynamics of the population are analogous to those of a component oscillator (Achuthan and Canavier 2009; Chandrasekaran et al 2011). For example, absence epileptic seizures have been postulated to arise from phase-locking with a small but noticeable phase lag between thalamic and cortical sites (Perez Velasquez et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…If the appropriate PRCs for neural oscillators can be measured, then we do not require any additional assumptions regarding the intrinsic dynamics of the oscillator or the form of the coupling. These results can be extended to apply to two populations of reciprocally coupled oscillators (Achuthan and Canavier 2009; Chandrasekaran et al 2011) under additional assumptions regarding the dynamics of each population.…”
Section: Introductionmentioning
confidence: 99%
“…Stability of the two cluster mode can be calculated by treating the two clusters as two oscillators, provided synchrony within each cluster is stable [37], otherwise a more complicated analysis applies [38]. Since we are only interested in cases in which synchrony is stable, this caveat is not relevant.…”
Section: Stable Synchrony But No Two Cluster Solutionmentioning
confidence: 99%